Side Variations of Anterior Cruciate Ligament Coronal Angles: Implications for ACL Reconstruction. Issue 8 (8th September 2019) - Mayer, Catherine; Barner, Kyle; Lorimer, Shannon; Tran, Quoc; Baer, Jacob; Keim Janssen, Sarah; McCumber, Travis; Wright, Barth
Abstract : Current literature has shown a biomechanical advantage of recreating the native coronal obliquity of the anterior cruciate ligament (ACL) during grating procedures; however, the majority of studies on ACL morphological variation have been performed unilaterally. This cadaveric study aimed to evaluate sided ACL coronal angle of inclination variation including trend analysis with sex, age, height, and femoral condyle width. The ACLs of 57 embalmed cadaveric specimens were evaluated bilaterally for a total of 114 ACLs. The knees were flexed to 110°. A 0.70‐mm wire measured coronal angulation through the lateral tibial plateau and the medial ACL border. An image taken of the wire allowed digital measurement with the ImageJ software. IBM SPSS was utilized for statistical analysis. Bilateral measurements demonstrated a difference in an individual's sided ACL angulation ( P < 0.001). Right‐sided angulation was greater in 61.4% (35/57). In cadavers with greater right‐side angulation, right ACLs averaged 66.2° versus left ACLs averaged 60.9° ( P < 0.001). Cadavers with greater left‐sided ACL angles demonstrated average left ACLs measuring 65.5° versus right ACLs measuring 60.6° ( P < 0.001). Right‐sided angles were greater in 69.7% of females. Understanding the anatomy of the ACL's native coronal angle and variations between a patient's knees is imperative during reconstruction surgery to aid in anatomic tunnel placement for improved knee motion and rotational knee kinematics following surgery. A statistically significant difference exists between an individual's right and left ACL coronal angles of inclination. Clin. Anat. 32:1102–1106, 2019. © 2019 Wiley Periodicals, Inc.